2019
DOI: 10.1002/adfm.201904557
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Materials with Atomic Precision: Artificial Atoms in Solids: Ab Initio Design, Control, and Integration of Single Photon Emitters in Artificial Quantum Materials

Abstract: This Progress Report explores advances and opportunities in the atomic-scale design, fabrication and imaging of quantum materials towards creating artificial atoms in solids with tailored optoelectronic and quantum properties. The authors outline an "ab initio" approach to quantitatively linking first-principles calculations and atomic imaging with atomic patterning, setting the stage for new designer quantum nanomaterials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 88 publications
1
15
0
Order By: Relevance
“…Moreover, tailoring correlation effects in nanostructure via a precise control of both the positioning and the composition of point defects would open the way to quantum metamaterials. This challenge benefits of the interplay between advanced experimental techniques and theoretical models able to predict the properties of interest [22]. Based on ab-initio calculations [3], some of us have recently demonstrated that GeV complexes in silicon are stable defects, characterized by excited states deep in the bandgap, at about −0.5 eV and −0.35 eV from the conduction band, consistent with experiment [23].…”
Section: Introductionsupporting
confidence: 52%
“…Moreover, tailoring correlation effects in nanostructure via a precise control of both the positioning and the composition of point defects would open the way to quantum metamaterials. This challenge benefits of the interplay between advanced experimental techniques and theoretical models able to predict the properties of interest [22]. Based on ab-initio calculations [3], some of us have recently demonstrated that GeV complexes in silicon are stable defects, characterized by excited states deep in the bandgap, at about −0.5 eV and −0.35 eV from the conduction band, consistent with experiment [23].…”
Section: Introductionsupporting
confidence: 52%
“…This challenge benefits of the interplay between advanced experimental techniques and theoretical models able to predict the properties of interest. [22] Based on ab initio calculations, [3] some of us have recently demonstrated that GeV complexes in silicon are stable defects, characterized by excited states deep in the bandgap, at about ≃−0.5 eV and ≃−0.35 eV from the conduction band, consistent with experiment. [23] Such impurity states have large on-site electron-electron repulsion (≃150 meV) due to their highly localized wavefunctions (the decay length of the lowest charged state is ≃0.45 nm).…”
Section: Introductionmentioning
confidence: 56%
“…This challenge benefits of the interplay between advanced experimental techniques and theoretical models able to predict the properties of interest. [ 22 ]…”
Section: Introductionmentioning
confidence: 99%
“…Lower-loss magnetic materials, such as V [TCNE] x with magnon damping rate two orders of magnitude lower than YIG's [49], could be used to boost the nanomagnonic cavityenhanced decay rate of the spin emitter and realize the strong-coupling regime where g Γ. By comparison, in spin emitters realized by defects in solidstate materials [50], phonon fields with frequencies also in the microwave range can be used to drive spin transitions [51] with Rabi frequencies on the order of 1-50 MHz [42,43], but these interactions can require careful control and engineering of phononic cavities.…”
Section: Magnon-emitter Couplingmentioning
confidence: 99%